The Art of Smearing: How Is Feminist Decolonizing Artivism Received by Italian Newspapers? The Case of Montanelli’s Statue - Mandolini, Nicoletta (2022)
On March 8, 2019, during a demonstration organised on occasion of the International Women's Day in Milan, members of the feminist collective Non Una Di Meno (not one woman less) Milano threw washable pink paint on the statue that commemorates the Italian journalist Indro Montanelli (1909–2001). The aim of exposing at a visual level the acclaimed writer’s controversial past was crucial to the group’s symbolic action. In fact, despite being a reference figure for many Italian intellectuals, Montanelli participated in the Abyssinian war in 1935 and, as a member of the fascist army, he engaged in a relationship with a 12-year-old local girl who acted as his wife and sexual object. The collective’s action, which can be labelled as a feminist decolonizing performance, has already been read as a form of artivism that manipulated the Italian’s artistic heritage with the objective of criticising the existing narrative on Italy’s colonial past. In this sense, an analysis of the resonance that journalistic coverage assigned to the event proves crucial for understanding the impact that such an action has had on Italian public opinion and the progress towards the country's mental decolonization. This article presents the findings of a qualitative analysis conducted on a corpus of 10 online newspaper articles published in the aftermath of the artivist performance on Montanelli’s statue. The study employs Foucauldian critical discourse analysis in order to identify the rhetorical strategies used by journalists to criticise or legitimate the feminist collective’s action. Among these strategies, particular attention is paid to those discursive techniques adopted to portray the act as a form of vandalism or, on the contrary, as a form of art. The aim is to show how the discourse on art versus non-art/vandalism is used to confirm (or overcome) the discursive limits imposed by the still dominant narratives on the nation’s colonial history as well as on the disposability of “othered” women’s bodies.